Cell-Type-Specific Differentiation and Molecular Profiles in Skin Transplantation: Implication of Medical Approach for Genetic Skin Diseases - Noritaka Oyama; Fumio Kaneko (Journal of Transplantation)
Skin is highly accessible and valuable organ, which holds promise to accelerate the understanding of future medical innovation in association with skin transplantation, engineering, and wound healing. In skin transplantation biology, multistage and multifocal damages occur in both grafted donor and perilesional host skin and need to be repaired properly for the engraftment and maintenance of characteristic skin architecture. These local events are more unlikely to be regulated by the host immunity, because human skin transplantation has accomplished the donor skin engraftment onto the immunocompromised or immunosuppressive animals. Recent studies have emerged the importance of α-smooth muscle actin- (SMA-) positive myofibroblasts, via stage- and cell-specific contribution of TGFβ, PDGF, ET-1, CCN-2 signalling pathways, and mastocyte-derived mediators (e.g., histamine and tryptase), for the functional reorganisation of the grafted skin. Moreover, particular cell lineages from bone marrow (BM) cells have been shown to harbour the diferentiation capacity into multiple skin cell phenotypes, including epidermal keratinocytes and dermal endothelial cells and pericytes, undercontrolled by chemokines or cytokines. From a dermatological viewpoint, we review the recent update of cell-type- and molecular-specific action associated with reconstitution of the grafted skin and also focus on the novel application of BM transplantation medicine in genetic skin diseases.